2021
DOI: 10.7326/m20-6817
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Adding a Mask Recommendation to Other Public Health Measures to Prevent SARS-CoV-2 Infection in Danish Mask Wearers

Abstract: Observational evidence suggests that mask wearing mitigates SARS-CoV-2 transmission. It is uncertain if this observed association arises through protection of uninfected wearers (protective effect), via reduced transmission from infected mask wearers (source control), or both. This randomized controlled trial investigates whether recommending surgical mask use when outside the home reduces wearers' risk for SARS-CoV-2 infection in a setting where masks were uncommon and not among recommended public health meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
307
1
7

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 352 publications
(322 citation statements)
references
References 34 publications
7
307
1
7
Order By: Relevance
“…Only 1 published randomized trial has evaluated a community mask recommendation to prevent SARS-CoV-2 infection—the DANMASK-19 (Danish Study to Assess Face Masks for the Protection Against COVID-19 Infection) trial ( 51 ). This trial was designed to evaluate only the protective effect to mask wearers and not source control.…”
Section: Evidence From Randomized Controlled Trials Remains Sparsementioning
confidence: 99%
“…Only 1 published randomized trial has evaluated a community mask recommendation to prevent SARS-CoV-2 infection—the DANMASK-19 (Danish Study to Assess Face Masks for the Protection Against COVID-19 Infection) trial ( 51 ). This trial was designed to evaluate only the protective effect to mask wearers and not source control.…”
Section: Evidence From Randomized Controlled Trials Remains Sparsementioning
confidence: 99%
“…The update searches identified 739 citations. One study ( 2 ) on the use of masks and the prevention of SARS-CoV-2 infection in a community setting and 2 studies ( 3 , 4 ) in health care settings were added for this update ( Supplement Tables 1 to 4 ).…”
mentioning
confidence: 99%
“…The evidence on any mask use versus no use and surgical mask use versus no use in community settings and risk for SARS-CoV-2 infection were previously assessed as insufficient on the basis of 2 (any mask use) or 1 (surgical mask use) observational studies with methodological limitations ( 5 , 6 ). A new, good-quality, open-label trial of 6024 community-dwelling adults in Denmark evaluated the effects of wearing a surgical mask outside of the house, at a time when mask wearing in the community was neither recommended nor common ( 2 ). The incidence of SARS-CoV-2 infection among participants (based on a positive IgM or IgG antibody result, a positive reverse transcriptase polymerase chain reaction test result, or an infection diagnosed in a health care setting) was 2.0%.…”
mentioning
confidence: 99%
“…Even so the added value of masks to social distancing remains unclear. The DANMASK study 11 wherein all participants were encouraged to socially distance in public reported only a 0.3% between‐group difference over 1 month in seroconversion rates, between no mask recommendation or a recommendation to wear a mask when outside the home for more than 3 h among other people (1.8% vs 2.1% seroconversion). On the other hand, household mask‐wearing in the pre‐symptomatic phase may be of great value, 12 although this too requires testing in prospective studies.…”
mentioning
confidence: 99%